Penggunaan Algoritma Naive Bayes Untuk Mengevaluasi Prestasi Akademik Mahasiswa Universitas Nusantara PGRI Kediri - Intan Nur Farida; Ratih Kumalasari Niswatin (Teknik Informatika, Politeknik Negeri Tanah Laut, 2017)
Students' academic activities result in achievements that can be known in each semester until the graduation stage. This study classifies student achievement in the appropriate graduation category or not in the fifth semester. As attributes used include attributes of origin, High School origin, employment and income of parents, Comrade Achievement Index (IPK) and Achievement Index (IP) semesters one to five. The purpose of this study is the application to obtain academic achievement of students Nusantara PGRI Kediri University uses the naïve bayes algorithm. Train data used is the data of student class 2010 to 2012 on the Faculty of Engineering, with a focus on Informatics Engineering courses. Next is calculated using naïve bayes algorithm to classify student achievement. While the test data using student academic data generation 2013. Research results Student's previous academic achievement. This research is useful to know the factors that influence student achievement that can be used to support the making of university policy, for example on the target of new student admission promotion.